2020
DOI: 10.36899/japs.2020.1.0016
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis and Expression Investigation of Steroleosin Gene Family in Arabidopsis Thaliana

Abstract: Despite having growing evidence discussing the role of steroleosins in crop plants, their systemic analysis has not been worked extensively. Therefore, bioinformatics tools were employed to study Arabidopsis (Arabidopsis thaliana) steroleosin in comparison with reported Brassica napus and pine steroleosins. Based on molecular weight, eight steroleosins in Arabidopsis were divided into two groups, L-steroleosin (alkalescence) and H-steroleosin (acidity except At5g50770). Phylogeny analysis suggested that H-ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…DNA segments that are nearly identical (90%-100%) and found on multiple genomic sites are referred to as segmental duplications (Khaja et al, 2006). Previous studies suggest that within Arabidopsis, AtHSD1a and AtHSD4a are found to be segments of AtHSD1b and AtHSD4b, respectively, which is due to the 33-kb duplication events on chromosome 5 (Baud et al, 2009;Aziz et al, 2020). Our study revealed that both segmental and tandem duplication were the reasons for HSD1s in plants.…”
Section: Potential Roles Of Hsds In Plant Speciesmentioning
confidence: 59%
See 4 more Smart Citations
“…DNA segments that are nearly identical (90%-100%) and found on multiple genomic sites are referred to as segmental duplications (Khaja et al, 2006). Previous studies suggest that within Arabidopsis, AtHSD1a and AtHSD4a are found to be segments of AtHSD1b and AtHSD4b, respectively, which is due to the 33-kb duplication events on chromosome 5 (Baud et al, 2009;Aziz et al, 2020). Our study revealed that both segmental and tandem duplication were the reasons for HSD1s in plants.…”
Section: Potential Roles Of Hsds In Plant Speciesmentioning
confidence: 59%
“…Expression analysis of two HSD genes, HSD1 and HSD5, shows that they are predominantly upregulated in seeds, which are the essential site for TAG assembly and are considered to provide energy for developing seeds. Thus, the high expression level of two HSDs in seeds provides more evidence for their involvement in triacylglycerol metabolism (Aziz et al, 2020). Fascinating to notice, A. hypochondriacus HSD1 and HSD5 are mainly upregulated in floral and seed tissues, while the maximum expression level of G. max HSD1 and HSD5a and b was only noticed in seed tissues (Table S3).…”
Section: Potential Roles Of Hsds In Plant Speciesmentioning
confidence: 66%
See 3 more Smart Citations